“We want integration but such that shows our part”: Ethnic activism among immigrants’ political-social leadership - Sharaby, Rachel (Advances in Social Sciences Research Journal, 2018)
This paper discusses the bi-polar identity of young leaders of immigrant groups from Morocco and Kurdistan in Israel, who led the struggle for legitimization of their culture and redefinition of the Israeli cultural space. They were, in fact, ‘cultural entrepreneurs’, who initiated and headed a cultural revival, and acted as pivotal change agents in the dynamics of continuing their ethnic tradition, while selectively returning to their ethnic origins. The syncretism that they adopted in the renewal of their ethnic celebrations facilitated an inter-generational, diachronic dialog as well as dialog with the ‘other’ outside their ethnic group.